The Effect of the Enteral Homeostasis Correction Program on the Hemorheological Pattern in Acute Poisoning With Corrosive Substances - M. M. Potskhveriya; K. K. Ilyashenko; M. V. Belova; E. E. Bitkova; A. Yu. Simonova (Неотложная медицинская помощь)
Background poisonings with corrosive substances in russia retains a high proportion among acute exotoxemias. They are accompanied by severe homeostasis disorders with changes in hemorheological pattern in particular.Aim of study To evaluate the effect of the enteral correction of homeostasis (ech) on the hemorheological patterns in patients with acute poisoning with corrosive substances.Material and methods Patients with chemical burns of the mucous membrane of the esophagus of the 2nd-3rd degree and stomach of the 2nd-3rd degree who were treated at the n.v. sklifosovsky research institute for emergency medicine in 2017–2021 were examined. In 73 patients, ech was performed (study group), and 35 patients received standard treatment (comparison group). Indicators of hemorheological status were examined on the 1st, 3rd and 5th days in the course of ongoing therapy, as well as before and after intestinal lavage in patients of the study group. Statistical data analysis was carried out using the statistica 10 software package (statsoft, inc., usa).Results The first stage of ech, characterized by the use of intestinal lavage, has no negative effect on hematocrit, plasma viscosity and erythrocyte aggregation indices.The use of a glucosated enteral solution led to a decrease in plasma viscosity under normal hematocrit conditions at all follow-up periods. In patients of both groups, there was a decrease in blood viscoelasticity under conditions of high shear potential at all stages of the study, which indicates violations of the deformability of red blood cells. This process is more significant in individuals of the comparison group. The conducted studies have shown that standard treatment and ech for poisoning with corrosive substances have a corrective effect on the hemorheological profile aimed at stabilizing blood circulation, however, according to a number of indicators, the effect of ech is more pronounced.Conclusion The program of enteral correction of homeostasis and standard treatment for poisoning with corrosive substances have a unidirectional effect on the indicators of the hemorheological pattern. In cases of application of the enteral homeostasis correction program, the outstripping improvement of the majority of the studied hemorheological parameters is seen.